THE DEVELOPMENT OF TOOLS TO ASSESS THE EFFECTIVENESS AND QUALITY OF CORPORATE GOVERNANCE OF NON-PUBLIC COMPANIES - B. S. Bataeva (Финансы: теория и практика, 2017)
The problem of evaluating the effectiveness and quality of corporate governance acquired a special urgency in connection with the need to develop universal tools that allow the most comprehensive analysis of the operational and strategic activities of companies with state participation, to defi ne the trends and prospects for their longterm development, commercial and budgetary effi ciency. In addition, the changed legal regulation of nonpublic and public companies, and the content of the procedure of joint-stock companies. Based on the methodology of strategic management in the article the features of goal setting in developing the strategy development of companies with state participation, grounded system of strategic planning, determined the content of the stages of the strategy process. The analysis of methodical base for the application of key performance indicators (KPI) for state companies on the basis of which the specifi city of the use of KPIs by public and nonpublic companies, the proposed evaluation system of quality management of non-public companies with state participation that includes the integral factors and indicators of quality of governance. As a tool for management by key performance indicators and evaluation, proposes the use of a balanced scorecard, discusses necessary conditions for its successful implementation in the companies with state participation. The proposed integral indicator of effi ciency of activity of joint stock companies and indicators of quality of management of unitary enterprises, can be the basis for evaluating the effectiveness of operational management of companies with state participation, to be used in the process of monitoring and ranking.